2015
DOI: 10.1007/s00167-015-3820-4
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of stem in revision of total knee arthroplasty: cemented versus cementless—a meta-analysis

Abstract: Systematic review of Level IV, Therapeutic studies, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 53 publications
(105 reference statements)
4
53
0
Order By: Relevance
“…42 The only meta-analysis addressing this question was performed by Wang et al When examining 17 observational studies, they found no superiority of either stem, with no significant difference in reoperation, aseptic loosening, and infection. 43 After a thorough evaluation of the best evidence in the literature, it is clear that no consensus can be made about cementing versus hybrid fixation of stems in rTKA. Each technique has its advantages and limitations.…”
Section: Outcomes and Conclusionmentioning
confidence: 99%
“…42 The only meta-analysis addressing this question was performed by Wang et al When examining 17 observational studies, they found no superiority of either stem, with no significant difference in reoperation, aseptic loosening, and infection. 43 After a thorough evaluation of the best evidence in the literature, it is clear that no consensus can be made about cementing versus hybrid fixation of stems in rTKA. Each technique has its advantages and limitations.…”
Section: Outcomes and Conclusionmentioning
confidence: 99%
“…In their study with 84 knee revisions, Lachiewizc et al found no significant difference between cemented and uncemented pediculated fixation when used in knee revisions due to loosening [21]. Similarly, a recent meta-analysis failed to demonstrate that any fixation technique was superior [22].…”
Section: Stem Fixation/stemsmentioning
confidence: 94%
“…Based on the available literature, no superiority of any type of stem fixation has been found26). Due to the inhomogeneity of failure mechanism, bone stock, implant design, and comorbidities, a strictly randomized controlled trial (RCT) for revision TKA is nearly impossible to compare the outcomes according to the cementation technique26). A recent RCT27) performed radiostereometric analysis with (1) constructs of the same length, (2) the same Anderson Orthopaedic Research Institute type of bone defect, (3) implants with the same level of constraint, and (4) exclusion of re-revision TKAs.…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques have their own advantages and disadvantages (Table 2)20,26). Based on the available literature, no superiority of any type of stem fixation has been found26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation